2020
DOI: 10.3389/fgene.2020.592588
|View full text |Cite
|
Sign up to set email alerts
|

Sanger Validation of High-Throughput Sequencing in Genetic Diagnosis: Still the Best Practice?

Abstract: Next-generation sequencing (NGS)’s crucial role in supporting genetic diagnosis and personalized medicine leads to the definition of Guidelines for Diagnostic NGS by the European Society of Human Genetics. Factors of different nature producing false-positive/negative NGS data together with the paucity of internationally accepted guidelines providing specified NGS quality metrics to be followed for diagnostics purpose made the Sanger validation of NGS variants still mandatory. We reported the analysis of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
0
22
0
1
Order By: Relevance
“…The number of studies comparing Nanopore and Sanger sequencing in diagnostics has been limited [ 31 33 ]. Routine diagnostics using Sanger sequencing, the current gold standard for point-mutation detection so far, revealed the presence of various SNPs, including the non-synonymous variants p.E148Q, p.R202Q, p.M694V, p.P369S and p.R408Q in this sample collective [ 34 ]. All of these mutations have been previously described in FMF patients [ 22 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies comparing Nanopore and Sanger sequencing in diagnostics has been limited [ 31 33 ]. Routine diagnostics using Sanger sequencing, the current gold standard for point-mutation detection so far, revealed the presence of various SNPs, including the non-synonymous variants p.E148Q, p.R202Q, p.M694V, p.P369S and p.R408Q in this sample collective [ 34 ]. All of these mutations have been previously described in FMF patients [ 22 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…By convention, NGS results necessitate validation by Sanger sequencing as the reference standard. However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [ 38 , 39 ]. Arteche-Lopez et al, reported their validation study of 1109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…By convention, NGS results necessitate validation by Sanger sequencing as the reference standard. However, recently the necessity of Sanger validation has been called into question for human genome sequencing by several studies [25,26]. Arteche-Lopez et al, reported their validation study of 1,109 NGS variants in 825 clinical exomes, the largest sample set to date using Illumina technology [25].…”
Section: Discussionmentioning
confidence: 99%